2015
DOI: 10.1039/c4en00107a
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and characterization of poly(ethylene oxide) templated nickel oxide nanofibers for dye degradation

Abstract: In the present study, one dimensional nickel oxide (NiO) nanofibers were successfully fabricated using an inexpensive and simplistic electrospinning technique to evaluate their efficient applicability as a photocatalyst in dye degradation processes. The synthesis part involves the calcination of electrospun poly(ethylene oxide)/ nickel acetate tetrahydrate nanofibers to obtain phase pure cubic NiO nanofibers, which were further characterized using various techniques to determine their physical and chemical pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(34 citation statements)
references
References 38 publications
(38 reference statements)
2
30
0
Order By: Relevance
“…The metal‐oxygen frequencies observed in this study are well matched with reported results . The mode present at 1135 cm −1 corresponding to the C−N stretching and remaining two modes 1615, 2348 cm −1 are assigned to the vibrations of water molecules …”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The metal‐oxygen frequencies observed in this study are well matched with reported results . The mode present at 1135 cm −1 corresponding to the C−N stretching and remaining two modes 1615, 2348 cm −1 are assigned to the vibrations of water molecules …”
Section: Resultssupporting
confidence: 92%
“…[30] The mode present at 1135 cm À 1 corresponding to the CÀ N stretching and remaining two modes 1615, 2348 cm À 1 are assigned to the vibrations of water molecules. [31] It is well known that band gap is a vital parameter in determining the characteristics of semiconductor materials which is recorded by UV absorption spectrum. Figure 2(b) shows the optical absorption spectrum of the NiO nanofibers at the room temperature.…”
Section: Resultsmentioning
confidence: 99%
“…The fact that CuO@Ag 0 displays negative Zeta potential in the entire pH range indicates a higher and more stable dispersion as compared to CuO. Even though this is a special feature of improved repulsion between similarly charged particles of metal loaded oxide [20,21], this must be mainly due to the disappearance of H-bridges between the particles as a result of the involvement of terminal OH groups of CuO in Ag:OH-interaction, as previously stated.…”
Section: Structural Changes Upon Agnps Incorporationmentioning
confidence: 54%
“…The role of carrier polymer is to adjust the viscosity of the solution used for fabrication of the electrospun nanofibers . Some of the commonly used polymers as carrier medium are poly(vinyl pyrrolidone) (PVP), poly(vinyl acetate), poly(ethylene oxide), polyacrylonitrile, and poly(vinyl alcohol) …”
Section: Introductionmentioning
confidence: 99%